Trial Design Considerations to Increase Older Adult Accrual to National Cancer Institute Clinical Trials. Issue 60 (15th December 2022) - Le-Rademacher, Jennifer; Mohile, Supriya; Unger, Joseph; Hudson, Matthew F; Foster, Jared; Lichtman, Stuart; Perlmutter, Jane; Dotan, Efrat; Extermann, Martine; Dodd, Kevin; Tew, William; Klepin, Heidi; et al.
Abstract: Although adults aged 65 years or older make up a strong majority of cancer patients, their underrepresentation in cancer clinical trials leads to the lack of representative data to guide evidence-based therapeutic decisions in this patient population. The Trial Design Working Group, convened as part of the workshop titled, Engaging Older Adults in the National Cancer Institute Clinical Trials Network: Challenges and Opportunities, recommended study designs and design elements that could improve accrual of older adults in National Cancer Institute–funded clinical trials. These include trials that are specifically designed to enroll older adults, trials that include a cohort of older patients (parallel cohort, stratified cohort, or embedded cohort), and trials with pragmatic design elements to facilitate enrollment of older adults. This manuscript provides brief descriptions of the recommended designs, examples of successful trials, and considerations for implementation of these designs. As with any clinical trial, the scientific questions and trial objectives should drive the study design, the selection of endpoints and intervention, and eligibility criteria. When designing trials that include older adults, the heterogeneity of fitness levels is an important consideration as fitness can influence accrual rates and outcomes. Appropriately incorporating geriatric assessments can help identify the optimal subset of older patients for inclusion and minimize selection bias. Incorporating pragmatic design elements to reduce the burden on trial participants as well as on accruing sites and retaining essential elements to ensure that the main goal of the trial can be accomplished can enhance enrollment without compromising the integrity of trials.